Effects of age and travel on National Football League quarterback performance: a correlational study - Morvant, B. A.; Heintz, E. C.; Foreman, J. J. (International Journal of Kinesiology & Sports Science, 2021)
Background: Long-distance travel is common for professional athletes; thus, the impact of jet-lag on athletic performance is a relevant topic. Additionally, older individuals take longer to recover from exercise and post-travel fatigue; therefore, it is likely that age and travel affect performance. Objective: The purpose of this study is to investigate the effects of age and travel on NFL quarterback performance. Method: A correlational research design is used to examine the effects of age and travel on NFL quarterback performance. Data were collected from pro-football-reference.com. Quarterback ratings from the 2018 NFL season are analyzed with age, distance traveled, season week, and weeks since the team`s bye week. The interaction of age and distance is also included to examine the impact of the age-distance relationship on performance. Regression analysis is used to predict quarterback ratings. Results: Season week (p = 0.04), weeks since a bye week (p = 0.041), and distance traveled (p = 0.031) have negative effects on quarterback ratings. The age-performance relationship in NFL quarterbacks is non-linear (p = 0.018), with quarterback performance decreasing during an athlete`s 20s and then increasing during an athlete`s 30s. Additionally, ratings of younger quarterbacks decrease with farther distances traveled, while the ratings of older quarterbacks increase with farther distances traveled (p = 0.072). Conclusions: Differences in performance by age with travel may be the result of different severities of jet-lag symptoms experienced by younger and older quarterbacks, as well differences in strategies for managing post-travel fatigue by athletes of different ages.